2008
DOI: 10.4012/dmj.27.612
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effect of Silver Powder in vivo

Abstract: The cytotoxicity of silver is a known property of this metal. Interestingly, in the cases of argyria and tattoos, Ag remains in the tissue for a long time without causing harm to the host except pigmentation. To understand these contradictions, pure silver implantation by an original subcutaneous injection method was performed. Two sizes of silver powder particles were implanted subcutaneously: 100 nm (P-silver) and the maximum 45 μm (G-silver). The sulfuration of silver and histopathologic changes were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Aoyagi and Katagiri also reported the presence of silver and sulfur in connective tissues without host reaction. Using an original subcutaneous injection method, Aoyagi and Iwasaki have implanted silver particles of two different sizes (100 nm and 45 μm) and have observed the sulfuration of silver and histopathologic changes during a year. From the obtained results, they concluded that the decline of silver effect on the host was correlated with an increase in the sulfuration of silver.…”
Section: Biocompatibility Of Silvermentioning
confidence: 99%
“…Aoyagi and Katagiri also reported the presence of silver and sulfur in connective tissues without host reaction. Using an original subcutaneous injection method, Aoyagi and Iwasaki have implanted silver particles of two different sizes (100 nm and 45 μm) and have observed the sulfuration of silver and histopathologic changes during a year. From the obtained results, they concluded that the decline of silver effect on the host was correlated with an increase in the sulfuration of silver.…”
Section: Biocompatibility Of Silvermentioning
confidence: 99%
“…However, the accumulation of a high amount of silver in the human body can cause argyria or argyrosis, which results from the deposition of significant amounts of insoluble silver precipitates in the dermis of the skin and the cornea or conjunctiva of the eyes [ 27 , 28 ]. However, no pathological damage to tissues can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for the Ag/Ir/Ti* sample with a developed surface and effective galvanopair, an increased number of macrophages is already observed. Apparently, these are initial or local manifestations of argyrosis [67,68]. On the contrary, the Ag/Au/Ti sample, where the silver oxide phase predominates, showed a less intense and more uniform (almost linear) dissolution of silver.…”
Section: In Vivo and In Vitro Biocompatibilitymentioning
confidence: 92%